Antimicrobial Peptides and Physical Activity: A Great Hope against COVID 19 - Laneri, Sonia (Microorganisms, 2021)
Antimicrobial peptides (AMPs), α- and β-defensins, possess antiviral properties. These AMPs achieve viral inhibition through different mechanisms of action. For example, they can: (i) bind directly to virions; (ii) bind to and modulate host cell-surface receptors, disrupting intracellular signaling; (iii) function as chemokines to augment and alter adaptive immune responses. Given their antiviral properties and the fact that the development of an effective coronavirus disease 2019 (COVID-19) treatment is an urgent public health priority, they and their derivatives are being explored as potential therapies against COVID-19. These explorations using various strategies, range from their direct interaction with the virus to using them as vaccine adjuvants. However, AMPs do not work in isolation, specifically in their role as potent immune modulators, where they interact with toll-like receptors (TLRs) and chemokine receptors. Both of these receptors have been shown to play roles in COVID-19 pathogenesis. In addition, it is known that a healthy lifestyle accompanied by controlled physical activity can represent a natural weapon against COVID-19. In competitive athletes, an increase in serum defensins has been shown to function as self-protection from the attack of microorganisms, consequently a controlled physical activity could act as a support to any therapies in fighting COVID-19. Therefore, including information on all these players’ interactions would produce a complete picture of AMP-based therapies’ response.